A IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) PADA TEMA GAYA HIDUP BERKELANJUTAN BERBASIS REUSE SISWA KELAS V SD NEGERI 02 MASBAGIK TIMUR: IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) PADA TEMA GAYA HIDUP BERKELANJUTAN BERBASIS REUSE SISWA KELAS V SD NEGERI 02 MASBAGIK TIMUR - Ulpatul Laeli; Andi Sulastri, Musabihatul Kudsiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study discusses the Implementation of the Pancasila Student Profile Strengthening Project (P5) on the theme of a Sustainable Lifestyle Based on Reuse for fifth grade students of SD Negeri 02 Masbagik Timur. The aim of this study is to identify the implementation, obstacles, and strategies in carrying out P5 sustainable lifestyle based on reuse in grade V. This research is a qualitative study with a descriptive method. Data were obtained through observation, interviews, and documentation. The research was conducted on fifth grade students at SD Negeri 02 Masbagik Timur. The sources of information in this study amounted to 8 people, consisting of six fifth grade students, one principal, and one homeroom teacher of grade V. The results of this study show that the implementation of P5 on the theme of a sustainable lifestyle based on reuse in fifth grade students was carried out through project-based activities by utilizing used materials into new products with functional value, such as straws made into flowers, used bottles turned into pencil holders, and cardboard made into frames that were later used to decorate the classroom. These activities were able to foster students’ creativity, environmental awareness, responsibility, and collaboration. However, the implementation of this project faced several obstacles, such as limited time, inadequate facilities and infrastructure, as well as differences in students’ abilities that affected group work. To overcome these obstacles, teachers applied collaborative learning strategies through discussion, hands-on practice, structured group division, and providing special guidance. The P5 activities not only produced products from used materials but also provided meaningful learning experiences for students in building the character of the Pancasila student profile and fostering sustainable lifestyle habits.